Experimental and computational studies on a three-membered diphosphido thorium metallaheterocycle [η5-1, 3-(Me3C)2C5H3]2Th[η2-P2(2, 4, 6-iPr3C6H2)2]. Issue 20 (30th April 2019) - Zhang, Congcong; Wang, Yongsong; Hou, Guohua; Ding, Wanjian; Zi, Guofu; Walter, Marc D.
Abstract : A three-membered diphosphido thorium metallaheterocycle complex was prepared and its reactivity was investigated. Abstract : A three-membered thorium metallaheterocycle [η 5 -1, 3-(Me3 C)2 C5 H3 ]2 Th[η 2 -P2 (2, 4, 6- i Pr3 C6 H2 )2 ] (4 ) is readily prepared besides H2 from [η 5 -1, 3-(Me3 C)2 C5 H3 ]2 Th(PH-2, 4, 6- i Pr3 C6 H2 )2 (3 ) upon heating in toluene solution. Density functional theory (DFT) studies were performed to elucidate the 5f orbital contribution to the bonding within Th-(η 2 -P-P) revealing more covalent bonds between the [η 5 -1, 3-(Me3 C)2 C5 H3 ]2 Th 2+ and [η 2 -P2 (2, 4, 6- i Pr3 C6 H2 )2 ] 2− fragments than those in the related thorium metallacyclopropene. Consequently, distinctively different reactivity patterns emerge, e.g., while4 reacts with pyridine derivatives such as 4-dimethyaminopyridnie (DMAP) and forms the DMAP adduct [η 5 -1, 3-(Me3 C)2 C5 H3 ]2 Th[η 2 -P2 (2, 4, 6- i Pr3 C6 H2 )2 ](DMAP) (5 ), it may also act as a [η 5 -1, 3-(Me3 C)2 C5 H3 ]2 Th(ii ) synthon when reacted with bipy, Ph2 S2 or Ph2 Se2 . Nevertheless, no reaction of complex4 with alkynes is observed, but it reacts as a nucleophile towards nitriles and aldehydes resulting in five- or seven-membered metallaheterocycles, respectively. DFT computations provide some additional insights into the experimental observations.